Long-Term Growth Driven by a Sequence of General Purpose Technologies - Daniel Schiess; Roger Wehrli (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
We present a Schumpterian model of endogenous growth with General Purpose Technologies (GPTs) that captures two important historical stylized facts: First, from the beginning of mankind until today GPTs are arriving at an increasing frequency and, second, all GPTs heavily depended on previous technologies. In our model, the arrival of GPTs is endogenous and arises stochastically depending on the currently available applied knowledge stock. This way of endogenizing the arrival of new GPTs allows for a model which is more in tune with the historical reality than the existing GPT models.
Keywords: O11; O33; O41; 330; Schumpeterian growth; research and development; general purpose technologies; Innovation; Wirkungsanalyse; Schumpeterismus; Endogenes Wachstumsmodell; Theorie